Aboveground Biomass and Nutrient Pools in Two Evergreen Oak Stands of the Middle Moroccan Atlas Area - Boulmane, Mohamed; Santa-Regina, Ignacio; Khia, Abderrahim; Abbassi, Hassan; Halim, Mohamed (Arid Land Research and Management, 2013)
The aboveground tree biomass and nutrient pools, litterfall, and weight loss of litter due to decomposition have been measured in two permanent plots of evergreen oak forest (Quercus ilex L.) of the Middle Moroccan Atlas area (Tafachna and Reggada). The aboveground biomass was estimated by cutting and weighing twenty trees Y (biomass)¼aX (X¼(D2H)b, D and H are respectively the diameter at 1.30m and tree height. The aboveground biomass of the two studied stands was: 96.0 and 86.4 t ha1, respectively, for Tafachna and Reggada of which the woody part accounts for approximately 96%. The average productions of litter are, respectively, 3030 and 3560 kg ha1 yr1 for Tafachna and Reggada. The leaves account for approximately 70% of the total litterfall, restored to the soil 38.3 kg ha1 yr1 for Tafachana and 44.6 kg ha1 an1 for Reggada (approximately 74% of the total nutrient amount of the litterfall). The decomposition pattern of the leaves litter from each site according to diameter classes. In order to establish biomass regression equations the best fit was obtained by applying the allometric method: follows a negative exponential equation of form RF¼A þB exp (kt). The nitrogen was the bioelement that contributed the greatest amount to the bio- geochemical cycling between vegetation and soil. At the level of internal exchange to the trees, translocation, and transfer, the nitrogen was followed by phosphorus and potassium.
Keywords: aboveground biomass; allometric method; forest ecosystem; litter decomposition; nutrient storage; Quercus ilex

Biomass models to estimate carbon stocks for hardwood tree species - Ruiz-Peinado Gertrudix, R; Montero, G; del Rio, M (Forest Systems; Vol 21, No 1 (2012), 2012)
To estimate forest carbon pools from forest inventories it is necessary to have biomass models or biomass expansion factors. In this study, tree biomass models were developed for the main hardwood forest species in Spain: Alnus glutinosa , Castanea sativa , Ceratonia siliqua , Eucalyptus globulus , Fagus sylvatica , Fraxinus angustifolia , Olea europaea var. sylvestris , Populus x euramericana , Quercus canariensis , Quercus faginea , Quercus ilex , Quercus pyrenaica and Quercus suber . Different tree biomass components were considered: stem with bark, branches of different sizes, above and belowground biomass. For each species, a system of equations was fitted using seemingly unrelated regression, fulfilling the additivity property between biomass components. Diameter and total height were explored as independent variables. All models included tree diameter whereas for the majority of species, total height was only considered in the stem biomass models and in some of the branch models. The comparison of the new biomass models with previous models fitted separately for each tree component indicated an improvement in the accuracy of the models. A mean reduction of 20% in the root mean square error and a mean increase in the model efficiency of 7% in comparison with recently published models. So, the fitted models allow estimating more accurately the biomass stock in hardwood species from the Spanish National Forest Inventory data.
Keywords: aboveground biomass; additivity; belowground biomass; biomass models; Carbon Sequestration; hardwood species